Whey protein isolate microgel properties tuned by crosslinking with organic acids to achieve stabilization of pickering emulsions - do Prado Silva, Jéssica Thaís [UNESP]; Benetti, João Vitor Munari [UNESP]; de Barros Alexandrino, Taís Téo; Assis, Odilio Benedito Garrido; de Ruiter, Jolet; Schroën, Karin; Nicoletti, Vânia Regina [UNESP] (MDPI, 2021)
Whey protein isolate (WPI) can be used effectively to produce food-grade particles for stabilizing Pickering emulsions. In the present study, crosslinking of WPI microgels using organic acids (tannic and citric acids) is proposed to improve their functionality in emulsions containing roasted coffee oil. It was demonstrated that crosslinking of WPI by organic acids reduces the microgels’ size from ≈ 1850 nm to 185 nm and increases their contact angle compared to conventional WPI microgels, achieving values as high as 60°. This led to the higher physical stability of Pickering emulsions: the higher contact angle and smaller particle size of acid-crosslinked microgels contribute to the formation of a thinner layer of particles on the oil/water (O/W) interface that is located mostly in the water phase, thus forming an effective barrier against droplet coalescence. Particularly, emulsions stabilized by tannic acid-crosslinked WPI microgels presented neither creaming nor sedimentation up to 7 days of storage. The present work demonstrates that the functionality of these crosslinked WPI microgels can be tweaked considerably, which is an asset compared to other foodgrade particles that mostly need to be used as such to comply with the clean-label policy. In addition, the applications of these particles for an emulsion are much more diverse as of the starting material.
Keywords: Citric acid; Particle properties; Protein microgels; Tannic acid; Whey protein isolate